DETERMINATION THE LEVEL OF SOCIAL SECURITY OF THE STATE: COMPARISON OF APPROACHES AND PROSPECTS OF DEVELOPMENT - Колесніков, А. П.; Зяйлик, М. Ф. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The plural amount of scientific approaches in estimation the level of social security in Ukraine and their partial difference from the official methodology testify the imperfection of official point of view. This research is dedicated to the characteristics of the special aspects of these differences; the discovering of the regularities of scientific approaches and the substantiation of the directions of optimization of the official methodology taking into account the developed proposals. The article deals with investigation of various scholars approaches to estimation the social security level in Ukraine and the comparison of their features with the official methodology was made. The commonality of the indicative approach to the evaluation of the subject is established. It is determined that the main disadvantage of the official methodology and scientific approaches is their almost exclusively factual nature and the failure to take into account certain methodological aspects of harmonization with European norms; particularly regarding the assessment of poverty level. The optimization of the methodology for estimation the level of social security foresees; apart from a part of the factual indicators; the implementation of dynamic alternative indicators of predictive nature. Using the reasonable indirect impact indicators (cyberspace impact; the intensity of the changing the level of shadow economy; the level of the middle class formation; the state of environmentally friendly economy) and further development of their criterion limits in official methodic recommendations will allow to estimate more deeply the threats to social security of Ukraine and qualitatively predict their dynamics in the future